How to reduce termination on freemium platforms—literature review and empirical analysis - Philipp Brüggemann; Nina Lehmann-Zschunke (Journal of Marketing Analytics, 2023)
In light of increasing digitization and monetization, the freemium pricing model is being used more and more frequently. Against a backdrop of increasing competition and rising costs to attract new users, freemium platform providers need to know how to reduce termination rates. We analyze several influencing factors of termination rates using extensive data over a 5-year period from a freemium platform on sport and breeding horses. We find that shorter contract terms, increasing involvement, and increasing platform-specific content reduces termination rates. Furthermore, freemium providers should pay special attention to the interaction of video views and number of last logins. While both variables individually have no significant influence, the interaction effect positively affects termination rates. The higher both the number of video views and the number of last logins, the higher the termination rate. For freemium providers this finding leads to a dilemma. In short term (within a week), they do not know if a premium user has logged in for the last time and is willing to terminate. Still, this result is highly relevant for freemium providers. They should use our results to analyze last logins and video views ex post. In this way, they can learn about their customers' behavior and find out how to reduce the termination rate in the future.
Keywords: 650; Freemium; Online marketing; Online platform; Premium; Retention; Termination